Before the Devil Breaks You - Book 3 - Bray, Libba (New York : Little, Brown and Company, 2017)
The Diviners face ghosts that are haunting an asylum and wreaking havoc all over New York City, forgotten ones with dangerous ties to the King of Crows.
Accelerated Reader AR